2017
DOI: 10.1186/s13071-017-2294-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of blastocystosis in Malaysia: does seasonal variation play an important role in determining the distribution and risk factors of Blastocystis subtype infections in the Aboriginal community?

Abstract: BackgroundAlternating wet and dry seasons may play an important role in the acquisition and distribution of Blastocystis subtype infection in the tropics. This cross-sectional study was therefore conducted to provide the prevalence of Blastocystis and to determine the potential risk factors associated with each subtype during the wet and dry seasons in the Aboriginal community, Pahang, Malaysia.MethodsA total of 473 faecal samples were collected: 256 (54.1%) and 217 (45.9%) samples were obtained during the wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
0
26
0
Order By: Relevance
“…Indeed, intestinal parasites are usually considered as vectors of poverty related diseases as highlighted for instance by the high prevalence of Blastocystis sp. revealed in low-income African [ 9 ], Asian [ 11 ], and American countries [ 13 ]. Moreover, the prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, intestinal parasites are usually considered as vectors of poverty related diseases as highlighted for instance by the high prevalence of Blastocystis sp. revealed in low-income African [ 9 ], Asian [ 11 ], and American countries [ 13 ]. Moreover, the prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of Blastocystis sp. is thus naturally favored by the precarious sanitary and hygienic conditions encountered in certain populations with low level of sanitation, particularly in African, Asian, or American developing countries [ 8 , 9 , 10 , 11 , 12 , 13 ]. On the other hand, the zoonotic potential of Blastocystis sp.…”
Section: Introductionmentioning
confidence: 99%
“…To date, ST8 has only been identified with regularity in some New World monkeys (Alfellani et al, 2013c). There are only sporadic reports of ST8 in humans (Forsell et al, 2017; Stensvold et al, 2008; Barbosa et al, 2018; Mattiucci et al, 2016; Stensvold et al, 2009b; Seguí et al, 2018), non-human primates (Alfellani et al, 2013c; Helenbrook et al, 2015; Scicluna et al, 2006), birds (Abe et al, 2003), other hosts (Noradilah et al, 2017a) and water (Noradilah et al, 2017b). Although ST8 has been reported once in bird droppings (Abe et al, 2003) the subtypes usually reported in birds are ST6 (Jacob et al, 2016) and ST7 (Stensvold et al, 2009b; Greige et al, 2018; Deng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…is thus much lower in industrialized countries than in lower-income geographical areas [ 5 ]. For instance, it reaches 10 to 20% in European countries [ 8 , 9 , 10 , 11 ] but can largely exceed 40–50% in various African [ 12 , 13 ], Asian [ 14 , 15 ], and American countries [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%